Does Pink October really impact breast cancer screening? - Marcelo Antonini; Denise Joffily Pereira da Costa Pinheiro; Gisela Rosa Franco Salerno; Ana Beatriz Tavares de Moura Brasil Matos; Odair Ferraro; André Mattar; Reginaldo Guedes Coelho Lopes; Juliana Monte Real (Elsevier, 2022)
Objective: This study aims to evaluate the impact of the Pink October Campaign on the increase in mammographic screening in Brazil. Study design: Ecological observational study, based on retrospective data. Methods: Brazilian national screening database (DATASUS/SISMAMA/Information System on Breast Cancer) was used as a data source and is publicly available for download and analysis. We report screening numbers and outcome rates from January 2017 to December 2021 comparing statistically (ANOVA test, post-Tukey test), age groups, regions of Brazil, and the four quarters of the year. Results: During the study period, the average number of exams performed monthly over the five years was 137,400.117. An increase in the number of mammograms performed in October was identified, as well as in the two following months, respectively 33%, 39%, and 22%, with statistical significance (p = 0.000) in relation to the three quarters of the year. In addition, in the other months, we found values below the monthly average. Statistical difference was not found in the increase in mammograms considering age groups (p = 0.5) and different regions of the country (p = 0.6). Conclusions: This study showed an increase in mammographic screening in the three months following the Pink October Campaign, so we should intensify similar actions throughout the year and not just in October.